Associated factors to the early death while on waiting list for liver transplantation in patients with low MELD score - Brasil, Ivelise Regina Canito (2006)
Introduction: Mortality on waiting list for liver transplantation is high around the world. In Brazil, 5.63 liver transplantation/million people were performed along 2005. With the recent implantation in Brazil of the severity according to the MELD score, there might be a reduction in the amount of death on waiting list. Purpose: This paper will analize the relationship between MELD score and hyponatremia or refractory ascites upon the registration on waiting list for liver transplantation of patients who died in the first six months of list. Patients and Methods: Analysis of 46 records of patients who died in the first 6 months on waiting list for liver transplantation was performed. It was assessed the age, gender, initial MELD score, serum sodium, refractory ascites, and time on the list until the death. Patients were divided in 2 groups: group A, patients with initial MELD score ³ 16, and group B those with initial MELD score <16. Both groups were compared as to the presence of refractory ascites and/or hyponatremia. Results: Mean time until death was 3 months. Total amount of patients in group A and B was 31 and 15 respectively. In group B, 93% patients showed either hyponatremia or ascites. There was no statistically significant difference as to the presence of hyponatremia and/or ascites between both groups. Conclusion: Most patients with MELD <16 who died in the first 6 moths on the waiting list had hyponatremia and/or refractory ascites.